The implementation of health operational cost management in reducing stunting in the Kalisat Community Health Centre, Jember Regency - Khikmah, Masilatul; Herawati, Yennike Tri; Baroya, Ni'mal (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background : BOK Funds are used to finance ten activities that promote and prevent health, including community health centre management and malnutrition reduction. Other sources of funding for stunting include the State Budget, the Local government budget, village funds, and the BOK. According to the 2018 Jember Regency BOK budget realization report, the average utilization of BOK funds by Jember Regency community health centres was 89.99%. This typical rate of absorption is regarded as satisfactory. This is not consistent with the increase in stunting, particularly at the Kalisat Community Health Centre, which increased by 25.07 % in 2019. Objectives : The objectives of the study were: a) to evaluate the planning; b) to evaluate the mobilization and implementation; and c) to evaluate the supervision, control, and performance evaluation of BOK in reducing stunting. Methods : Therefore, this study employed a qualitative methodology and case study research design. Informants involved in this research were the head of the community health center a person in charge of the BOK, secretary and a member of the BOK management, the head of administration, nutritionist at the community health center, and regional midwife. Completed research conducted in August of 2020. An interview guide, in-depth interviews were utilized to collect data. Results : According to the study's found that the series of management activities were in accordance with the guidelines. Planning is carried out from the bottom up, Mobilization and Implementation are carried out through Lokmin, but Lokmin participants are often absent due to multiple tasks (e.g., there were several activities that did not go according to plan, particularly during the pandemic era, there were double jobs, and workshop participants were frequently late.) BOK is used to finance the operational costs of stunting prevention program activities.Conclusions: Planning, mobilization, implementation and use of BOK funds are in accordance with guidelines and budget allocation. Mini workshops should be held at agreed times and take into account officers who have double jobs